2020
DOI: 10.3390/cancers12030648
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Combined All-Trans Retinoic Acid and Arsenic Trioxide Treatment of Acute Promyelocytic Leukemia Cells and Further Enhancement by Inhibition of Atypically Expressed Transglutaminase 2

Abstract: Randomized trials in acute promyelocytic leukemia patients have shown that treatment with a combination of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) is superior in efficacy to monotherapy, with significantly decreased mortality. So far, there are little data available to explain the success of the ATRA and ATO combination treatment in molecular terms. We showed that ATRA-and ATO-treated cells had the same capacity for superoxide production, which was reduced by two-thirds in the combined treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The latter feature of NC9 is particularly relevant, if we consider that the TGH isoform of the enzyme is still capable of hydrolysing GTP, albeit with low binding efficiency [12]. NC9 has been shown to irreversibly block both functions, especially in cancer types [45,[47][48][49]55,56]. Our data demonstrated that the choice to use NC9 in combined treatments proved effective, driving MDA-MB-231 cells to early apoptosis and MCF-7 and T47D cells to late apoptosis, limiting the progression of cell cycle but inducing accumulation of cells in different phases, depending on the type of cell, while also decreasing NF-ĸB in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter feature of NC9 is particularly relevant, if we consider that the TGH isoform of the enzyme is still capable of hydrolysing GTP, albeit with low binding efficiency [12]. NC9 has been shown to irreversibly block both functions, especially in cancer types [45,[47][48][49]55,56]. Our data demonstrated that the choice to use NC9 in combined treatments proved effective, driving MDA-MB-231 cells to early apoptosis and MCF-7 and T47D cells to late apoptosis, limiting the progression of cell cycle but inducing accumulation of cells in different phases, depending on the type of cell, while also decreasing NF-ĸB in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with NC9 were performed on BrCa cells to verify whether the action of Doxo depends on an accumulation of TG2 as in other types of cancers [45][46][47][48][49]. In this approach NC9 was added at 30 μM concentration (K i value) for 16 h, after 24 h of treatment with Doxo for a total exposure time of 40 h. In this way we studied the effects of this drug combination on the expression of NF-ĸB in MCF-7 and MDA-MB-231 cells.…”
Section: Effects Of Doxo-mediated Tg2 Induction Were Limited By Nc9 Inhibitormentioning
confidence: 99%
“…Cystamine inhibits LPS-induced liver injury TG2 is mainly expressed and activated in midzonal F4/80/CD80+ M1 macrophages in the livers of septic mice ⇧ Promoting [22] Cystamine inhibits neuroinflammation in amyotrophic lateral sclerosis TG2 catalyzes the oligomerization of superoxide dismutase 1 and induces TNF-α, IL-1β, and nitric oxide in microglial cells ⇧ Promoting [107] Cystamine ameliorates TNBS-induced colitis in a rat model of inflammatory bowel disease TG2 activity is associated with the production of mucosal TNF-α and serological IL-6 ⇧ Promoting [108] Cystamine rescues defective CFTR-induced cystic fibrosis TG2 catalyzes the crosslinking of beclin 1, leading to the sequestration of phosphatidylinositol-3-kinase complex III, accumulation of p62, and aggresome formation ⇧ Promoting [109] NC9 NC9 reduces pro-inflammatory cytokine production in combined ATRA and ATOtreated APL cells TG2 leads to inflammation, which is probably due to reactive oxygen species production ⇧ Promoting [116] ⇧, promoting role in inflammation or sepsis; ⇩, protective role in inflammation or sepsis; APL, acute promyelocytic leukemia; ATO, arsenic trioxide; ATRA, all-trans retinoic acid; CFTR, cystic fibrosis transmembrane conductance regulator; DC, dendritic cell; EC, endothelial cell; IFN-γ, interferon-γ; IL-1β, interleukin-1β; IL-17, interleukin-17; iNOS, inducible nitric oxide synthase; KO, knockout; LPS, lipopolysaccharide; MPTP, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine; MSU, monosodium urate; NFκΒ, nuclear factorκΒ; PMN, polymorphonuclear leukocyte; TGF-β, transforming growth factor-β; TNBS, 2,4,6-trinitrobenzene sulfonic acid; UV, ultraviolet.…”
Section: Cystaminementioning
confidence: 99%
“…These novel irreversible inhibitors of TG2, such as NC9 and VA4 [ 114 ], which specifically react with Cys-277 in the TG2 transamidation site and inhibit both transamidation and GTP-binding activities, are potent anticancer agents that inhibit the survival of cancer stem cells [ 115 ]. Very recently, an in vitro study showed that NC9 effectively reduced the levels of pro-inflammatory cytokines such as monocyte chemotactic protein 1, IL-1β, and TNF-α, in combined all-trans retinoic acid and arsenic trioxide-treated acute promyelocytic leukemia cells [ 116 ]. Evidence for genetic and pharmacological inhibition of TG2 during inflammation and sepsis is summarized in Table 1 .…”
Section: Targeting Tg2 In Inflammation and Sepsis: Evidence From Pmentioning
confidence: 99%
“…Differentiation syndrome, which develops in approximately 5–25% of APL patients, is a life-threatening condition triggered by a release of inflammatory cytokines and chemokines by blastic cells; these differentiate in response to ATRA and/or ATO therapy. An original article of this special issue demonstrates that atypical expression of the enzyme transglutaminase 2 (TG2) leads to the generation of inflammation, and could serve as a potential target for the prevention of differentiation syndrome [ 7 ].…”
mentioning
confidence: 99%